Hubungan Pengetahuan tentang Antibiotik terhadap Kepatuhan Penggunaan Antibiotik pada Mahasiswa Prodi Hukum di Universitas Esa Unggul - Ayu Limas; Antonius Dewanto Purnomo; Maksum Maksum (Syntax Idea)
Knowledge about antibiotics will influence each individual's compliance with antibiotic use. The higher the knowledge, the higher the compliance with antibiotic use and this will reduce the number of cases of antibiotic resistance. This study aims to determine the relationship between knowledge about antibiotics among law study program students at Esa Unggul University. This research is quantitative research using designcross-sectional with a sample of 320 respondents and respondent data that complies with the inclusion criteria of 129 respondents. Therefore, the data used was 129 respondents. The results obtained were that the majority of Esa Unggul University law study program students' knowledge level was high at 77.5%, followed by moderate knowledge at 10.1% and low knowledge at 12.4%. The majority of Esa Unggul University law study program students' compliance level is high 57.4%, followed by moderate compliance 17.8% and low compliance 24.8%. Test carried outchi squareThere is a relationship between knowledge about antibiotics and adherence to antibiotic use with a significance value of 0.001. Respondents with low knowledge had low compliance (100% were in the low compliance category). In contrast, respondents with high knowledge showed a more varied distribution where the majority had high compliance (74.0%), and a small portion had moderate (20.0%) and low compliance (6.0%).